Almas malditas na noite: o desespero nas narrativas curtas de horror gótico de Álvares de Azevedo e Edgar Allan Poe - Gottardi, Marina Gonçalves (2022)
This research proposes to analyze the presence of despair in four short stories of gothic fiction published in the nineteenth century; examining how this theme is portrayed in the text and its importance for the appeal of the genre. The four stories selected were authored by two pioneers of the Americas: “Solfieri'' and “Gennaro”, both from the anthology “Noite na Taverna” (1855) by Álvares de Azevedo, and “The Black Cat” (1843) and “The Raven” (1846) by Edgar Allan Poe. The project’s main question was whether despair would be common to all narrators and, should that be confirmed, how would this state of spirit be worked in the texts. The initial hypothesis was that the presence of despair and the ways in which it is built are part of the heart and soul of these texts and studying about it could bring about insights about their timeless appeal. Divided into three chapters, the dissertation starts with definitions of both gothic fiction and despair, as well as a presentation of the four selected stories. In the second chapter, we trace the line which connects the idea of despair according to Kierkegaard and Gaiman to gothic fiction. This is accomplished by means of a study of the history of humanity’s fears and icons of faith supported by texts by Jean Delumeau, Jane Ellen Harrison, among others. Then, the discoveries brought about by this study are correlated with the literary theory of texts by Edgar Allan Poe, Maurice Blanchot and Michel Collot. The third chapter contains the analysis of the stories under the light of the theory and discussions from the previous chapters. The comparative analysis of the stories and the theoretical survey confirm the hypothesis, as they have revealed that not only is despair common to all of the selected stories, it is also deeply rooted with the foundations of the genre